Impact of Motivation and Job Satisfaction on Employees Performance In the Education Sector With Mediating role of Organization Culture - Maryam Yousaf; Sidra Bibi; Muqadas Yaseen; Sadaf Muneer (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2024)
The primary objective of this research is to examine the relationship between motivation and employee performance. Moreover, the purpose of this study is to examine the role of job satisfaction in job performance. Furthermore, the objective is to examine the mediating role of organizational culture in the relationship between job satisfaction and employee performance. This study employs a quantitative research design. The research approach of this study is deductive. The population of this research consists of employees at Thal University Bhakkar. A sample size of 300 participants was required for adequate statistical power. A simple random sampling technique was used in this research. Researchers used SPSS and Smart PLS SEM for data analysis. The current study findings show that there is a significant role of motivation on employee performance. Furthermore, the findings also show that there is a significant role of job satisfaction as a stronger predictor of employee performance than motivation. Lastly, the findings show that there is a significant mediating role of organizational culture between motivation and job satisfaction on employee performance.